FISH analysis of numerical chromosomal abnormalities in the sperm of robertsonian translocation der(13; 14)(q10;q10) carriers - Zhu, Saijuan; Zhu, Yong; Zhang, Feng; Wu, Junping; Chen, Ying; Sun, Yijuan; Fu, Jing; Wu, Jiangnan; Xiao, Min; Zhang, Shuo; Zhou, Jing; Lei, Caixia; et al. (Frontiers in Genetics, 2022)
Fluorescence in situ hybridization analysis of numerical chromosomal abnormalities in the sperm of Robertsonian translocation der(13;14)(q10;q10) carriers has focused on a limited number of chromosomes mainly on chromosome 13, 18, 21, X, and Y. Here, we aimed to expand the analysis to all chromosomes by increasing the number of probes analyzed in fluorescence in situ hybridization. The incidence of numerical abnormalities of all chromosomes (1-22, X, and Y) was determined in sperm from 10 carriers of the Robertsonian translocation der(13;14)(q10;q10) and 10 normozoospermic males to fully assess the effect of translocation-derived chromosome on the segregation of all chromosomes during meiosis. Numerical abnormalities of the two translocated chromosomes were frequently detected in the sperm of der(13;14) translocation carriers, with an average frequency of 14.55±6.00% for chromosome 13 and 13.27±4.14% for chromosome 14. Numerical abnormalities of nontranslocated chromosomes, with an average frequency of 1.77±0.62% (range, 1.16–3.73%), was lower than that of translocated chromosome. However, the cumulative numerical abnormality of the 22 nontranslocated chromosomes was comparable to that of the two translocated chromosomes. Significantly increased numerical abnormalities in der(13;14) translocation carriers compared with those in normozoospermic males indicates the presence of translocation-derived chromosome disturbances, with translocated chromosomes being most affected; nontranslocated chromosomes were also affected, but to a lesser extent due to a mild interchromosomal effect.